(untitled) (Islas, 2023)
Introduction: This article is a study of fixed expressions (or polylexical units) found in the council records of the 19th century from the City Council of Santa Clara (1869-1873). It falls within the fields of Spanish language history and linguistic analysis of historical documents. The analysis is synchronous, covering a five-year period during the initial stage of the Ten Years’ War. Methods: A non-experimental descriptive cross-sectional study was conducted using theoretical methods (historical-logical, analytic-synthetic, inductive-deductive, and systemic-structural) and empirical methods (classic document analysis) along with techniques like literature review. Results: Semantic peculiarities of locutions, collocations, routine formulas, and other fixed structures from the cultured norm of Spanish during that period are observed. Apart from typical legal discourse expressions, there are, to a lesser extent, those related to general language and orality. Conclusions: The council records not only consist of schematized judicial formulas but also include expressions of varying degrees of abstraction. The presence of transparent metaphorical motivation in their semantic structures is noted.